New Perspectives in Optical Design (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The field of optical design has seen significant advancements in recent years, driven by the increasing demand for high-performance optical systems in various applications. New materials, fabrication techniques, and computational tools are enabling researchers to explore novel approaches to optical design that have the potential to revolutionize the field. This reprint showcases the latest research and developments in optical design, highlighting innovative concepts, methodologies, and applications. Key areas covered in this reprint include advanced materials, coatings, and process technology for optical components; computational methods and algorithms for optical design; integrated optics and photonic devices; and novel optical systems and applications.